2002
DOI: 10.1023/a:1015123024113
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Direct intra-articular injection of a PLGA nanosphere system with a water-soluble steroid provided a prolonged pharmacological efficacy in the joints of arthritic rabbits. The local anesthetic in the knee-joints was evaluated to be safe and without biologic damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…They determined that fluorescein-loaded nanoparticles (~265 nm in diameter) were readily phagocytosed and thus caused a very minimal immunogenic response from local tissue. However, microparticles (~26 μm average diameter, but ranging from 3.1–59.9 μm) were poorly phagocytosed resulting in the formation of large granulation tissue by multinucleated giant cells (Horisawa et al 2002). Conversely, Liggins and colleagues found nearly the opposite to be true.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They determined that fluorescein-loaded nanoparticles (~265 nm in diameter) were readily phagocytosed and thus caused a very minimal immunogenic response from local tissue. However, microparticles (~26 μm average diameter, but ranging from 3.1–59.9 μm) were poorly phagocytosed resulting in the formation of large granulation tissue by multinucleated giant cells (Horisawa et al 2002). Conversely, Liggins and colleagues found nearly the opposite to be true.…”
Section: Discussionmentioning
confidence: 99%
“…These strategies include encapsulation of drug in natural materials, such as chitosan, alginate, albumin protein, and elastin-like polypeptides, as well as synthetic materials such as polymers and lipids. Polymeric, drug-loaded particles, such as those constructed from materials such as poly-(lactide-co-glycolide) acid (PLGA) have been most widely studied for the delivery of small molecules to the joint space, and are now the subject of a clinical trial for the delivery of triamcinolone (Butoescu et al 2009, Horisawa et al 2002, Kumar 2013, Liang et al 2004). Similarly, liposomes have been developed to release dexamethasone following delivery to the joint space (Butoescu et al 2009, Lopez-Garcia et al 1993, Turker et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable microparticles composed of polyesters (for example, PGLA, PLLA), polyanhydrides, and polycaprolactones have been developed for broader clinical applications, including the encapsulation of synthetic hormones (Lupron®, Abbott), tretinoin (RetinA Micro®, OrthoNeutrogena) and risperidone (Riseperdal®, Janssen Pharma) and have shown potential for prolonging intra-articular drug residence time in preclinical studies. For betamethasone 56,58 , methotrexate 60 , diclofenac 59 , siRNA 136 and paclitaxel, 57 for example, encapsulation in microspheres composed of PLLA, PLGA, or polycaprolactones contributed to a sustained release effect in animal models of arthritis that could be observed up to 21 days after delivery in some cases. 5660 …”
Section: Intra-articular Therapeuticsmentioning
confidence: 99%
“…For betamethasone 56,58 , methotrexate 60 , diclofenac 59 , siRNA 136 and paclitaxel, 57 for example, encapsulation in microspheres composed of PLLA, PLGA, or polycaprolactones contributed to a sustained release effect in animal models of arthritis that could be observed up to 21 days after delivery in some cases. 5660 …”
Section: Intra-articular Therapeuticsmentioning
confidence: 99%
“…Poly(lactic- co -glycolic acid) (PLGA) has been widely employed to fabricate parenteral particulate systems, because of its long clinical use, favorable degradation characteristics, and sustained drug release profile 9,10. Horisawa et al11 revealed that PLGA-based nanoparticles (NPs) could prolong anti-inflammatory action of a corticosteroid, betamethasone sodium phosphate, by delaying the clearance rate of the active compound from the synovial cavity. Nevertheless, generally, NPs smaller than 250 nm in size quickly escape from the joint cavity, and thus longer retention times are still needed to permit less frequent IA injection 12.…”
Section: Introductionmentioning
confidence: 99%